2021
DOI: 10.1177/14034948211056209
|View full text |Cite
|
Sign up to set email alerts
|

The Faroese Septuagenarians cohort: A comparison of well-being before and during the COVID-19 pandemic among older home-dwelling Faroese

Abstract: Aims: Despite success in avoiding morbidity and mortality in the oldest members of the population during the COVID-19 pandemic, the crisis may have affected the well-being of older adults, for example due to social distancing measures. The aim of this study was to examine the well-being of older Faroese by conducting a direct comparison of well-being indicators on the same group of elderly people before and during the COVID-19 pandemic. Methods: Data were collected from 227 home-dwelling adults aged 82–86 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…One study addressed older adults living in the Faroe Islands (Eliasen et al, 2022). In total, 227 people aged between 82 and 87 were included in the telephone interviews.…”
Section: Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study addressed older adults living in the Faroe Islands (Eliasen et al, 2022). In total, 227 people aged between 82 and 87 were included in the telephone interviews.…”
Section: Older Adultsmentioning
confidence: 99%
“…Most of these people stayed in voluntary isolation at home. The prevalence of loneliness at the end of the irst wave increased from 7 per cent two years before the pandemic to 22 per cent in June-July 2020 (Eliasen et al, 2022). However, the assessment basis of loneliness changed from a self-administered questionnaire before the pandemic to a telephone interview during the pandemic.…”
Section: Older Adultsmentioning
confidence: 99%
“…Several studies investigated whether loneliness in older people increased during COVID-19 lockdowns. Most longitudinal studies that compared the lockdown in spring 2020 to the time before the COVID-19 pandemic found that loneliness increased in the older people [ 6–12 ]. Only few longitudinal studies found no such change in loneliness or only in subgroups [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%